Genome-wide identification and functional prediction of silicon (Si) transporters in poplar (Populus trichocarpa) - Md Mahmudul Hassan; Samir Martin; Kai Feng; Timothy B. Yates; Guoliang Yuan; Madhavi Z. Martin; Stanton Martin; Wellington Muchero; Natalie A. Griffiths; David J. Weston; Xiaohan Yang (Plant Biotechnology Reports, 2023)
Silicon (Si) enhances plant tolerance to various biotic and abiotic stressors such as salinity, drought, and heat. In addition, Si can be biomineralized within plants to form organic carbon-containing phytoliths that can have ecosystem-level consequences by contributing to long-term carbon sequestration. Si is taken up and transported in plants via different transporter proteins such as influx transporters (e.g., Lsi1, Lsi6) and efflux transporters (e.g., Lsi2). Additionally, the imported Si can be deposited in plant leaves via silicification process using the Siliplant 1 (e.g., Slp1) protein. Functional homologs of these proteins have been reported in different food crops. Here, we performed a genome-wide analysis to identify different Si transporters and Slp1 homologs in the bioenergy crop poplar ( Populus trichocarpa Torr. and A. Gray ex W. Hook). We identified one channel-type Si influx transporter (PtLsi1; Potri.017G083300), one Si efflux transporter (PtLsi2; Potri.012G144000) and two proteins like Slp1 (PtSlp1a; Potri.004G168600 and PtSlp1b; Potri.009G129900 ) in the P. trichocarpa genome. We found a unique sequence (KPKPPVFKPPPVPI) in PtSlp1a which is repeated six times. Repeated presence of this sequence in PtSlp1a indicates that this protein might be important for silicification processes in P. trichocarpa. The mutation profiles of different Si transporters in a P. trichocarpa genome-wide association study population identified significant and impactful mutations in Potri.004G168600 and Potri.009G129900 . Using a publically accessible database ( http://bar.utoronto.ca/eplant_poplar/ ), digital expression analysis of the putative Si transporters in P. trichocarpa found low to moderate expression in the anticipated tissues, such as roots and leaves. Subcellular localization analysis found that PtLsi1/PtLsi2 are localized in the plasma membrane, whereas PtSlp1a/PtSlp1b are found in the extracellular spaces. Protein–Protein interaction analysis of PtLsi1/PtLsi2 identified Delta-1-pyrroline-5-carboxylate synthase (P5CS) as one of the main interacting partners of PtLsi2, which plays a key role in proline biosynthesis. Proline is a well-known participant in biotic and abiotic stress tolerance in plants. These findings will reinforce future efforts to modify Si accumulation for enhancing plant stress tolerance and carbon sequestration in poplar.

Emerging Technologies and Approaches for In Situ, Autonomous Observing in the Arctic - Craig Lee; Michael DeGrandpre; John Guthrie; Victoria Hill; Ron Kwok; James Morison; Christopher Cox; Hanumant Singh; Timothy Stanton; Jeremy Wilkinson (Oceanography, 2022)
Understanding and predicting Arctic change and its impacts on global climate requires broad, sustained observations of the atmosphere-ice-ocean system, yet technological and logistical challenges severely restrict the temporal and spatial scope of observing efforts. Satellite remote sensing provides unprecedented, pan-Arctic measurements of the surface, but complementary in situ observations are required to complete the picture. Over the past few decades, a diverse range of autonomous platforms have been developed to make broad, sustained observations of the ice-free ocean, often with near-real-time data delivery. Though these technologies are well suited to the difficult environmental conditions and remote logistics that complicate Arctic observing, they face a suite of additional challenges, such as limited access to satellite services that make geolocation and communication possible. This paper reviews new platform and sensor developments, adaptations of mature technologies, and approaches for their use, placed within the framework of Arctic Ocean observing needs.

The practice and economics of hybrid poplar biomass production for biofuels and bioproducts in the Pacific Northwest - Brian J. Stanton; Andrew Bourque; Mark Coleman; Mark Eisenbies; Rachel M. Emerson; Jesus Espinoza; Carlos Gantz; Austin Himes; Andrew Rodstrom; Rich Shuren; Rick Stonex; Timothy Volk; et al. (BioEnergy Research, 2021)

A specific dietary fibre supplementation improves cognitive performance—an exploratory randomised, placebo-controlled, crossover study - Kirsten Berding; Caitriona M. Long-Smith; Carina Carbia; Thomaz F. S. Bastiaanssen; Marcel van de Wouw; Niamh Wiley; Conall R. Strain; Fiona Fouhy; Catherine Stanton; John F. Cryan; Timothy G. Dinan (Psychopharmacology, 2021)

Differential effects of psychotropic drugs on microbiome composition and gastrointestinal function - Sofia Cussotto; Conall R. Strain; Fiona Fouhy; Ronan G. Strain; Veronica L. Peterson; Gerard Clarke; Catherine Stanton; Timothy G. Dinan; John F. Cryan (Psychopharmacology, 2019)

Kilo Nalu: Physical/Biogeochemical Dynamics Above and Within Permeable Sediments - Francis Sansone; Geno Pawlak; Timothy Stanton; Margaret McManus; Brian Glazer; Eric DeCarlo; Marion Bandet; Jeffrey Sevadjian; Kevin Stierhoff; Christopher Colgrove; Andrew Hebert; In Chieh Chen (Oceanography, 2008)

Radiation hybrid mapping of 70 rat genes from a data set of differentially expressed genes - Caroline A. Wallace; Saira Ali; Anne M. Glazier; Penny J. Norsworthy; Danilo C. Carlos; James Scott; Tom C. Freeman; Lawrence W. Stanton; Anne E. Kwitek; Timothy J. Aitman (Mammalian Genome, 2002)